OPTICAL COHERENCE TOMOGRAPHY ANGIOGRAPHY ASSESSMENT OF VASCULAR EFFECTS OCCURRING AFTER AFLIBERCEPT INTRAVITREAL INJECTIONS IN TREATMENT-NAIVE PATIENTS WITH WET AGE-RELATED MACULAR DEGENERATION - Mastropasqua, Leonardo; Toto, Lisa; Borrelli, Enrico; Carpineto, Paolo; Di Antonio, Luca; Mastropasqua, Rodolfo (Retina (Philadelphia, Pa.), 2017)
To investigate vessel changes occurring after aflibercept injections in treatment-naive exudative age-related macular degeneration patients. Fifteen eyes of 15 patients affected by wet age-related macular degeneration were enrolled in the study. All the patients had a diagnosis of Type 1 choroidal neovascularization and were treated with 3 monthly aflibercept intravitreal injections (IVI). Subjects were evaluated by means of optical coherence tomography angiography at baseline, the day after the first injection and one month after both the first and the second IVI. At last, all the patients were followed up to 2 months after the third IVI. Foveal superficial vascular plexus flow density was 29.01% (21.13-37.32%) at baseline and was significantly reduced as soon as 1 month after the first IVI (median: 20.78%; interquartile range: 14.75-23.13%; P = 0.017). Parafoveal superficial vascular plexus flow density was 47.09% (44.91-51.72%) at baseline and significantly decreased as soon as 1 month after the second IVI (median: 44.40%; interquartile range: 41.59-49.29%; P = 0.034). Choroidal neovascularization lesion area remained stable throughout the follow-up. Nevertheless, interestingly, choroidal neovascularization flow area was significantly reduced as soon as the next day the first IVI (median: 0.37 mm and interquartile range: 0.27-0.72 mm at baseline; median: 0.30 mm and interquartile range: 0.24-0.64 mm at 1 day after the first IVI; P = 0.047). Intravitreal aflibercept injections are associated with a significant change in native retinal and choroidal vasculature. Moreover, the treatment did not cause a reduction in lesion area, but rather reduced the flow in the choroidal neovascularization.